Impact of British Colonial Economic Policies on Indonesia’s Trade and Agricultural Systems in the Early 19th Century - Jesika Indah Sari Purba; Desta Riani br Perangin-angin; Santa Hoky br Sembiring; Rosmaida Sinaga (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The British colonial administration in the early 19th century profoundly reshaped Indonesia’s trade and agricultural systems. This study examines the economic policies introduced under British rule, particularly during Sir Stamford Raffles’ administration, and their impact on Indonesia’s economic transformation. It focuses on key reforms implemented during the British occupation of Java (1811–1816), including changes to trade routes and agricultural policies. The central inquiry explores how these policies influenced local commerce and agricultural practices, with an emphasis on the introduction of the land rent system and the restructuring of the export sector. Employing a historical research approach, this study draws from primary sources such as government records and colonial reports, as well as secondary literature. The findings indicate that British policies accelerated the commercialization of agriculture, altered trade dynamics, and introduced new taxation structures that significantly disrupted traditional economic systems. However, these reforms also placed substantial economic pressures on local communities, exacerbating social inequalities and economic distress. While British interventions yielded short-term economic benefits, they simultaneously set the stage for prolonged colonial exploitation, shaping Indonesia’s economic trajectory in the decades that followed.